Friction Characteristics of Nanocoated Biomedical 316L Stainless Steel with Tantalum, Niobium, and Vanadium Under Wet Conditions (Journal of Engineering, 2025)
Reducing friction between orthodontic components, such as archwires and brackets, is crucial in contemporary orthodontic treatments. Coating these components is a significant method to achieve this goal. This research is aimed To investigate the tribological performance of nanocoated 316L stainless steel (SS)—one of the most widely used alloys in orthodontic archwire manufacturing—coated with vanadium (V), tantalum (Ta), and niobium (Nb) via plasma sputtering at varying time intervals (1, 2, and 3 hours) under wet conditions simulating an oral in-service environment, which is unexplored previously in the existing literature. Using a computerized tribo-system applying 1 N for 20 minutes on coated SS substrates, the common alloys for orthodontic archwire manufacturing. Results: The results indicated that the coefficient of friction (CoF) increased generally under wet conditions as a result of hydrogen bonding and capillary adhesion. Ta emerged as the preferred coating, demonstrating substantial friction reduction compared to Nb and V. V was found to have a negative tribological impact. This work concluded that Coating 316L SS with Ta was identified to improve tribological behavior in wet conditions that simulate an oral environment, potentially minimizing the duration of orthodontic treatment and promoting efficient tooth movement.